Political Rituals of Socialist Yugoslavia in Goran Tribuson’s Novels - Dragičević, Marijana (Anafora, 2025)
In analyzing three novels by Goran Tribuson—Povijest pornografije (1988), Ne dao Bog većeg zla (2002), and Vrijeme ljubavi (2017), all of which focus on the coming of age, the 1960s pop-culture, and the disintegration of generational ideals—this paper aims to interpret political rituals of socialist Yugoslavia. A special emphasis is placed on the portrayal of the Pioneer organization, which prepared children from the first grade of elementary school for participation in the socialist life of the so-called “new socialist man.” This complex phenomenon is examined by linking romantic movements (wherein ritual foundations can be observed) and by analysing literature as a source, all supported by current historiographical research. In seeking excerpts essential for the reception of political rituals, this paper points to symbolic actions, ceremonies, and behaviours conducted within the political context to establish, strengthen, and legitimize the state at a time when the author himself was a child and a member of the Pioneer Union. The temporal congruence provides an authentic historiographical basis with the political imagery of socialist Yugoslavia. The author’s critical distance is evident in the discourse of the dominant order through irony, mockery, and the transformation of everyday life into literary prose.